2008
DOI: 10.1080/07357900701840212
|View full text |Cite
|
Sign up to set email alerts
|

5-Aza-2-deoxycytidine Restores Proapoptotic Function of p53 in Cancer Cells Resistant to p53-induced Apoptosis

Abstract: The expression of p53-target genes encoding the proapoptotic factor Noxa, but not PUMA, was not induced by p53 in HCT116 and SW480 cells, which show resistance to apoptosis in response to p53 overexpression. The lack of p53 inducibility of Noxa was restored by treatment with the DNA methyltransferase inhibitor 5-Aza-2'-deoxycytidine (5-aza-CdR). Furthermore, p53 induced apoptosis in HCT116 and SW480 cells treated with 5-aza-CdR. Moreover, the inhibition of Noxa expression by RNAi in 5-aza-CdR-treated HCT116 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In this work we have highlighted the marked ability of CP to inhibit cell viability of colon cancer cell, mostly characterized by the predominance of antiapoptotic factors or defects in apoptosis effectors. In particular, among all cell lines, CP was highly effective even against SW480 and DLD1 colon cancer cells, in which mutation of p53 gene or high expression of mitochondrial COX‐2, respectively, conferred resistance to apoptosis [43, 44]. CP ability to trigger an apoptosis‐independent stress response represents an interesting property that may expand its spectrum of action towards aggressive cancers characterized by apoptosis resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In this work we have highlighted the marked ability of CP to inhibit cell viability of colon cancer cell, mostly characterized by the predominance of antiapoptotic factors or defects in apoptosis effectors. In particular, among all cell lines, CP was highly effective even against SW480 and DLD1 colon cancer cells, in which mutation of p53 gene or high expression of mitochondrial COX‐2, respectively, conferred resistance to apoptosis [43, 44]. CP ability to trigger an apoptosis‐independent stress response represents an interesting property that may expand its spectrum of action towards aggressive cancers characterized by apoptosis resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of p53AIP1 is primarily regulated by p53. Activation of p53 by a number of factors, such as DNA damage, induces the transcription of p53AIP1 (7)(8)(9)(10). In contrast to the p53-mediated regulation of p21 and MDM2, which involves the phosphorylation of Ser-15 of p53 (11,12), induction of p53aip1 mrna and its apoptotic function was uniquely associated with the phosphorylation of Ser-46 of p53 (4).…”
Section: Introductionmentioning
confidence: 99%
“…NOXA is a p53-target gene and NOXA regulates p53-dependent apoptosis [ 56 , 66 ], which is an important tumor suppressor mechanism of p53 [ 67 ]. We previously found that the induction of NOXA by p53 was suppressed in some colon cancer cells that show resistance to apoptosis by p53 overexpression and that lack NOXA inducibility by p53 was restored by 5-azacytidine [ 68 ]. These findings indicated the possibility that the expression of transcription factor(s) that induce NOXA is suppressed by methylation.…”
Section: Discussionmentioning
confidence: 99%